Sistemática de Stypiura Kirby e Parastypiura Steffan (Hymenoptera: Chalcididae) - Freitas, Juliana Martins da Silva (2020)
Stypiura and Parastypiura (Hymenoptera: Chalcididae) are two Neotropical genera that represent almost all Phasgonophorini in the region. This tribe has a worldwide distribution and the species with known biology are parasitoids of xylophagous beetle, an u